STRUCTURAL-CONTENT ASPECTS OF THE FORMATION OF UNIVERSITY'S INTERNAL MODEL OF EDUCATION QUALITY EVALUATION - Viktoria Moreva; Elena Tamoshkina; Marina Bogdanova (Вестник Северо-Кавказского федерального университета, 2022)
The article reveals the structural and content aspects of the education quality assurance system of in higher education. Based on the analysis of international and national standards of education quality management, the article presents the vision of the university quality evluation model that can ensure the high quality of education, the development of the potential of students and the competitiveness of the educational organization.